A statistical theory of gravitating body formation in extrasolar systems - Krot, Alexander (Cambridge Scholars Publishing, 2021)
This book develops the statistical mechanics of the formation of gravitating cosmogonical bodies in the investigation of our solar system and other exoplanetary systems. The first part of the text acquaints the reader with the developing statistical theory of gravitating cosmogonical body formation. Within the framework of this theory, the models and evolution equations of the statistical mechanics are proposed, while well-known problems of gravitational condensation of infinite distributed cosmic substances are solved on the basis of the proposed statistical model of spheroidal bodies.